Biogeography and integrative taxonomy of Epipterygium (Mniaceae, Bryophyta). Issue 6 (26th September 2020) - Hanusch, Maximilian; Ortiz, Edgardo M.; Patiño, Jairo; Schaefer, Hanno
Abstract: A significant number of bryophyte species are thought to have transcontinental geographic ranges, often with multiple disjunct distribution areas. One of these cases is Epipterygium tozeri (Mniaceae), with a Holarctic distribution and disjunct ranges in western North America, the Mediterranean, Japan and central Asia. Collections from different geographic regions were lumped into E. tozeri based on morphology, but a molecular confirmation was lacking so far. Here, we tested species concepts in the genus Epipterygium, with a special focus on the E. tozeri species complex, combining morphological and DNA sequence data for the nuclear ribosomal ITS region and two plastid loci ( trnG intron, trnT‐psbD spacer). In a second step, we reconstructed the historical biogeography of the genus. We found that Epipterygium most likely originated in Asia or North/Central America and that the alleged single widespread species E. tozeri with disjunct ranges is in fact a group of genetically and morphologically distinct taxa, including four overlooked species, for which we provide descriptions: E. atlanticum sp. nov., E. biauritum sp. nov., E. oreophilum sp. nov., and E. yunnanense sp. nov. The biogeographical history of these species is best explained by a step‐wise parallel colonization of the Eurasian and American continents followed by in‐situ speciation.